Application of Ranging Difference Location Algorithm in Wireless Sensor Network Location - Xiang, Bo (International Journal of Online and Biomedical Engineering (iJOE), 2017)
<span style="color: black; font-family: 'Times New Roman',serif; font-size: 10pt; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: DE; mso-bidi-language: AR-SA; mso-themecolor: text1;" lang="EN-US">A kind of location technologies are developed used in the sensor network monitoring, the existing RSSI location algorithm are analyzed, and a localization method is proposed based on the SSDOA ranging difference method. hyperbolic equations are constructed and Chan's algorithm is used to solve the coordinates of unknown nodes. The simulation model of ranging error location algorithm is established by MATLAB. By analyzing the effect of ranging accuracy on positioning accuracy, the positioning performance of classical RSSI localization algorithm is compared. The results show that the WSN localization algorithm based on the SSDOA has a good localization performance and can meet the localization requirements of some WSN applications. Based on the above finding, It is concluded that Chan's algorithm is suitable for wireless sensor networks based on TDOA localization algorithm.